Primary epithelioid angiosarcoma of bone: A case report with immunohistochemical study - Kudva Ranjini; Perveen Shahin; Janardhana Aithala (Wolters Kluwer Medknow Publications, 2010)
Primary malignant vascular tumors of the bone are exceedingly rare and represent <1% of primary malignant bone tumors. Angiosarcoma is a malignant mesenchymal neoplasm in which the neoplastic cells demonstrate endothelial differentiation. Epithelioid angiosarcoma (EA) is a rare variant of angiosarcoma that is characterized by large cells with an epithelioid morphology. EA is an aggressive tumor with poor prognosis. Here, we present a case of a 62-year-old man who had primary EA of the left tibia. He was treated with amputation and chemotherapy. After 1 month of chemotherapy, he developed pleural effusion and died.